Predictors of New-Onset Epilepsy in People With Younger-Onset Neurocognitive Disorders - Wang, Xinshi; Loi, Samantha M.; Foster, Emma; Chen, Zhibin; Velakoulis, Dennis; Kwan, Patrick (Frontiers in Aging Neuroscience, 2021)
Objective: People with neurocognitive disorders (NCDs) have an increased risk of epilepsy. However, most studies investigating the risk of seizures in people with NCDs are limited to those with Alzheimer’s disease (AD) and vascular dementia (VD), and those who developed dementia after age 65 years. A knowledge gap exists regarding factors associated with development of epilepsy in people with younger-onset NCD, and those with non-AD and non-VD dementia subtypes. In this study, we aimed to identify the factors associated with the development of epilepsy in people with younger-onset NCDs of varied etiologies, the majority of whom had symptom onset prior to age 65 years. Participants and Methods: This was a retrospective study reviewing the medical records of consecutive people admitted with cognitive impairment to a tertiary neuropsychiatry unit between 1 January 2004 and 30 April 2019. People diagnosed with primary NCDs were included in the analysis. The prevalence and characteristics of epilepsy were described. The factors associated with developing epilepsy were identified in a binary logistic regression model. Results: A total of 427 people were included. 114 had Alzheimer’s disease, 104 frontotemporal dementia, 51 vascular dementia, 69 movement disorder-associated dementia, and 89 unspecified NCD. The median age on admission was 59 years (range 33 to 86) and 75.2% (n=321/427) had young-onset NCD with onset before 65 years of age. 40/427 (9.4%) people had epilepsy, and epilepsy onset clustered between 2 years before and 6 years after the onset of cognitive decline in 80% (n=32/40). The most frequent seizure type was focal to bilateral tonic-clonic seizure (35%, n=14/40). Most of the people (94.7%, n=36/38) achieved seizure freedom with one or two antiseizure medications. People with unspecified NCD (compared to frontotemporal dementia and movement disorder-associated dementia, age of onset of NCDs ≤ 50 years, and current smoking status were independently associated with higher risk of developing epilepsy. Conclusion: Epilepsy is common in people with younger-onset NCDs, and a high index of suspicion is warranted particularly for those with unspecified subtype and smoking status. Smoking reduction or cessation should be further investigated as a potentially modifiable factor for risk reduction.